2019
DOI: 10.1177/0004563219856031
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-based contrast agents: A clinically significant analytical interference in inductively coupled plasma mass spectrometry elemental analysis

Abstract: Background Gadolinium-based contrast agents (GBCAs) have been used in magnetic resonance imaging for the past 30 years, where they have significantly improved the effectiveness of imaging studies. However, the increased usage of gadolinium in the medical community has also resulted in unexpected interferences in other laboratory assays. This has been particularly the case in clinical elemental analysis using inductively coupled plasma mass spectrometry (ICP-MS). Methods By conducting ICP-MS interference experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Since their clinical approval and introduction in 1988, GBCAs have been administered in 750 million standard doses (Bayer Healthcare, estimated from multiple internal and external sources). Several interferences on laboratory tests have been described, ranging from commonly used laboratory tests [ 12 ] to more specialized laboratory tests [ 18 ]. The probably most clinically relevant interference is the interference of GBCAs on serum calcium measurement by specific colorimetric assays.…”
Section: Resultsmentioning
confidence: 99%
“…Since their clinical approval and introduction in 1988, GBCAs have been administered in 750 million standard doses (Bayer Healthcare, estimated from multiple internal and external sources). Several interferences on laboratory tests have been described, ranging from commonly used laboratory tests [ 12 ] to more specialized laboratory tests [ 18 ]. The probably most clinically relevant interference is the interference of GBCAs on serum calcium measurement by specific colorimetric assays.…”
Section: Resultsmentioning
confidence: 99%
“…Day et al. 17 reported an approximately 15% reduction in signal for gallium, germanium, yttrium and rhodium in the presence of 1000 mg/L gadolinium. This gadolinium level is significantly higher than that typically observed in samples collected post MRI, however.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Day et al. 17 reported 42 cancelled serum selenium requests within one year at the Department of Laboratory Medicine and Pathology, Mayo Clinic, Rochester, MN, USA. Implementation of a correction equation approach to gadolinium interference will significantly reduce the time and cost associated with such recollections and lead to improved patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental quantitation of Gd interferences was investigated this year by a series of Gd spiking experiments. 150 In this work, Day et al demonstrated the space charge effect of Gd on internal standard elements Ga, Ge, Rh and Y by analysing urine samples spiked with 1000 ppm Gd. Analysis of spiked samples demonstrated positive interference in Se measurements from Gd at concentrations >10 000 ppm due to the double charge effect of 156 Gd on 78 Se.…”
Section: Elements As Tags For Indirect Determinationsmentioning
confidence: 95%